THE DEVELOPMENT OF CYLINDRICAL DIELECTRIC RESONATOR ANTENNA ARRAY - BABA, AFFAN AZIZ (2013)
In today's communication era, small size, wideband and high gain antennas are the requirement to meet high capacity and efficient long distance communication. In this thesis, experimental study on linear aperture and mutual coupled cylindrical dielectric resonator antenna (CDRA) arrays for ISM band has been presented. The antennas presented possess properties of small size, wideband, high gain, low back side radiation and good front to back ratio.